Financial Information System (FIS) / Kuan Chien Wee - Kuan, Chien Wee (2001)
Financial Information System for the Faculty of Computer Science and Information Technology (FCSIT-FIS) is a clien/server system introduced as a sub-system in the e-Faculty project. Its main purpose is to create a paperless, web-based system by providing on-line functions that allow users to access to FCSIT financial information. The main functions of FCSIT-FIS are: on-line spending request, financial information retrieval and account maintenance. FCSIT -FIS will be developing using ASP technology, VBScript, JavaScript and HTML language. Microsoft SQL Server will be use as the database server of the system.